Suicidal Behavior in Inmates through the Pathway of Psychopathy and Depression - Muller-Balazsfi, Zsofia (2017)
Prison inmates are more prone to commit suicide than are individuals in the general population. Current scientific research has identified risk factors of suicide in the general population, such as mood disorders, but only a few research studies have examined risk factors that are particularly relevant to the incarcerated population. This study used a quantitative archival research design to examine the effect of primary and secondary psychopathic personality traits on the development of suicidal behavior in the mentally ill male prison inmate population at a U.S. federal prison located in the Southeast. Data on psychopathic traits as measured by the Psychopathy Checklist-Revised, and on depression as measured by the Personality Assessment Inventory, together with information on the number of suicide attempts coming from prison medical files, were gained from an archival database. The sample size was 203 participants where data were previously collected during their pretrial evaluation. The study was guided by Mann's diathesis-stress model of suicide, according to which impulsive-aggressive personality traits, both of which are characteristics of psychopathy, elevate the risk for suicide. Furthermore, depression may serve as the stress component of the model, and thus its effect was also added to the standard multiple regression model in the analysis. During the analysis, a pattern emerged in which the effect of secondary psychopathic traits was moderated by the percent of time spent in solitary confinement. The results of this research contribute to positive social change by helping professionals working with this population to address the issue of suicide prevention in prison settings via more effective treatment programs